Penggunaan Garam Beriodium Tingkat Rumah Tangga di Kecamatan Sibolga Utara, Kota Sibolga - Chahyanto, Bibi Ahmad; Purba, Dorce Dame; Sasmita, Rita (Badan Penelitian dan Pengembangan Kesehatan, 2017)
The use of iodized salt in the household is highly recommended because of the iodine function that is essensial for the human body. This survey aims to test the iodine content qualitatively and study the use of iodized salt at the household level in North Sibolga sub-district, Sibolga city.The analytical survey with cross sectional design was conducted in 19 integrated service posts (POSYANDU) located in the working area of Pintu Angin Public Health Centre (PUSKESMAS Pintu Angin) in November 2016. The respondents in this survey were representatives of household member who came to POSYANDU and brought the salt commonly consumed by family. A total of 237 respondents were interviewed. Respondents were interviewed using structured questionnaire. Rapid test of iodine content in salt using reagent kit (PT Kimia Farma) was done to test he iodine qualitatively. Survey results show that all of households of respondents use salt in packs that have labeled âiodized saltâ or similar statements. However, from iodine rapid test results found 2.5% of households whose iodine content in ithe salt has been lost. The quality of iodine content in salt at the household is significantly influenced only by salt storage (open or closed).AbstrakPenggunaan garam beriodium di rumah tangga sangat dianjurkan karena fungsi iodium yang sangat penting bagi tubuh manusia. Survei ini bertujuan untuk menguji kandungan iodium secara kualitatif serta mempelajari penggunaan garam beriodium di tingkat rumah tangga di Kecamatan Sibolga Utara, Kota Sibolga. Survei analitik dengan desain cross sectional ini dilakukan di 19 Pos Pelayanan Terpadu (Posyandu) yang berada di wilayah kerja Puskesmas Pintu Angin pada bulan November 2016. Responden dalam survei ini adalah perwakilan anggota keluarga rumah tangga yang datang ke Posyandu serta membawa garam yang biasa dikonsumsi oleh keluarga. Total rumah tangga yang menjadi responden sebanyak 237. Responden diwawancarai menggunakan kuesioner secara terstruktur. Tes cepat kandungan iodium dalam garam menggunakan pereaksi kit (PT. Kimia Farma) dilakukan untuk menguji kandungan iodium secara kualitatif. Hasil survei menunjukkan bahwa seluruh rumah tangga responden menggunakan garam dalam kemasan yang telah mencantumkan label âGaram Beriodiumâ atau pernyataan sejenisnya. Namun, dari hasil tes cepat iodium ditemukan 2,5% rumah tangga yang kandungan iodium dalam garamnya telah hilang. Kualitas kandungan iodium dalam garam di tingkat rumah tangga secara signifikan hanya dipengaruhi oleh cara penyimpanan garam (terbuka atau tertutup).